2018
DOI: 10.1021/acs.jpclett.8b00516
|View full text |Cite
|
Sign up to set email alerts
|

Dye-Sensitized Downconversion

Abstract: Splitting one high-energy photon into two lower energy photons through downconversion has been demonstrated for a variety of combinations of rare earth (RE) ions. However, the low absorption cross section of RE3+ 4f–4f transitions hampers practical application. Therefore, enhancing the absorption by sensitization is crucial. We demonstrate efficient dye-sensitized downconversion using a strong blue/UV absorbing Coumarin dye to sensitize downconversion of the Pr3+–Yb3+ couple in NaYF4 nanocrystals (NCs). Lumine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 35 publications
2
42
0
Order By: Relevance
“…Very recently, dye-sensitized downconversion luminescence (DCL) has also been fulfilled. 30 Accordingly, dye sensitization of Ln 3+ -doped nanoparticles opens great opportunities for many applications. 31−33 At present, existing studies demonstrated either increased UCL or increased excitation range, and there is still a lack of general understanding of the dye−UCNPs interactions, with many remaining problems to be solved.…”
mentioning
confidence: 99%
“…Very recently, dye-sensitized downconversion luminescence (DCL) has also been fulfilled. 30 Accordingly, dye sensitization of Ln 3+ -doped nanoparticles opens great opportunities for many applications. 31−33 At present, existing studies demonstrated either increased UCL or increased excitation range, and there is still a lack of general understanding of the dye−UCNPs interactions, with many remaining problems to be solved.…”
mentioning
confidence: 99%
“…More recently, organic dyes have been reported in sensitization of down-converters and not only for the solar cells themselves, in so-called dye-sensitized systems. Reported used dyes to enhance downconversion so far include UV-blue absorbing Coumarin [102], fluorescein isothiocyante [103] and a dicyanostilbene derivative [104]. This field is still in its infancy, as it requires advanced synthesis, combining several material classes in a controlled manner.…”
Section: Sensitizationmentioning
confidence: 99%
“…The Pr 3+ / Yb 3+ down-conversion pair has already been realized in Gd3(Al, Ga)5O12 [114], LiYF4[106] and YF3 [80]. There are moreover a few reports on using organic dyes to sensitize the Pr 3+ / Yb 3+ couple, most successfully done with Coumarin on the surface of NaYF4: Pr 3+ , Yb 3+ nanoparticles [102].…”
Section: The Pr +3 / Yb 3+ Down-conversion Pairmentioning
confidence: 99%
“…A broad range of materials have been considered as quantum cutters for PV applications, including quantum dots [13][14][15][16] , organic dyes [17][18][19][20] , rare-earth compounds [21][22][23][24] and more recently perovskite compounds 25 . These different systems perform down-conversion through different microscopic processes, such as singlet fission, resonant energy transfer, impact ionization or cascade emission (see Fig.…”
Section: Introductionmentioning
confidence: 99%